Total pancreatectomy with islet cell autotransplantation in a 2‐year‐old child with hereditary pancreatitis due to a PRSS1 mutation. Issue 11 (4th August 2021) - Marfil‐Garza, Braulio A.; Hefler, Joshua; Dajani, Khaled; Kin, Tatsuya; James Shapiro, A. M.
Abstract : Acute recurrent and chronic pancreatitis in children carries high morbidity and burden. Compared to adults, ~75% of the cases of chronic pancreatitis in children are associated with underlying genetic mutations. The decision to intervene and the optimal timing poses unique challenges. Total pancreatectomy and islet cell autotransplantation (TPIAT) provides definitive therapy to relieve pain and improve quality of life while minimizing the risk of pancreatogenic diabetes. Substantial clinical data are available for adults; however, information on clinical outcomes in children remains scarce, particularly for very young children. Herein, we present an unusual, complex case of a 2‐year‐old child that underwent a successful TPIAT due to hereditary pancreatitis with an underlying mutation in PRSS1 gene, complicated by unremitting pancreatic ascites, hemorrhage, and sepsis. This is the youngest case to be reported in the literature. We provide a comprehensive report of the course and procedures implemented in this patient to guide other teams when considering these extraordinary measures in similar cases. Abstract : This case report highlights both the challenges and successful outcome of pancreatectomy with islet autotransplantation in an atypical but complex 2‐year‐old child with hereditary pancreatitis.